Analisis Pengaruh Dana Pihak Ketiga (DPK), Capital Adequacy Ratio (CAR), Non Performing Loan (NPL) dan Loan To Deposit Ratio (LDR) terhadap Penyaluran Kredit Perbankan - Mesrawati Mesrawati; Widya Hitajulu; Salsabila Siregar; Venny Venny; Sri Rejeki Panggabean; Feberius Halawa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
Commercial banks have the main activity in raising funds and channeling funds to the public. The biggest source of funds from commercial banks is the activity of channeling credit to the public. The purpose of this research is to find out and analyze DPK, CAR, NPL and LDR on bank credit distribution (Case Study at Commercial Banks listed on the Indonesia Stock Exchange Period 2014-2018). Quantitative research approaches are used by being a cause and effect relationship between independent and dependent variables. Documentation becomes a data collection technique. The population in this study were 45 commercial banks listed on the Indonesia Stock Exchange in 2014-2018. The research sample is 27 commercial bank companies listed on the Indonesia Stock Exchange in the 2014-2018 period with a sample of 135 observations. Multiple linear regression became the model of this study. The results of this study are DPK, CAR, NPL and LDR partially and simultaneously and significantly on bank loans (Case study on commercial banks listed on the Indonesia Stock Exchange in the period 2014-2018). Keywords : third party fund, capital adequacy ratio, non performing loan and loan to deposit ratio, credit distribution